6(2x+4)=42

Simple and best practice solution for 6(2x+4)=42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x+4)=42 equation:


Simplifying
6(2x + 4) = 42

Reorder the terms:
6(4 + 2x) = 42
(4 * 6 + 2x * 6) = 42
(24 + 12x) = 42

Solving
24 + 12x = 42

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-24' to each side of the equation.
24 + -24 + 12x = 42 + -24

Combine like terms: 24 + -24 = 0
0 + 12x = 42 + -24
12x = 42 + -24

Combine like terms: 42 + -24 = 18
12x = 18

Divide each side by '12'.
x = 1.5

Simplifying
x = 1.5

See similar equations:

| 2x-4+4x+10=9x-9 | | 2600+30x=2400+50x | | 109=5x+9 | | 41=2w+15 | | -3x/2=5 | | h=-28t^2+56t+4 | | (4+2i)(5-3i)= | | x/8=-41 | | -3/4(-12) | | X^2=1+i | | 30+x=2x+12 | | 3x-9=-43-10x | | 31=-x/5 | | (8+2i)-(6-4i)-(9-10i)= | | 4v-17=15 | | 5(5+3x)-10x=8 | | 12y+5=3(4y-5) | | 4x^3=256 | | 5x+x=780 | | 35=5/2x | | (10+5i)-(6-2i)+(3+4i)= | | x-3.1=2.1 | | 4x26/5 | | 3n^2+12n-8=7 | | 15/7=5x | | -1-4(-7+8x)=-2x-6 | | 8x+3y-6x-y= | | 4x-3=12-1x | | 15y-4=60-y | | 3x-7=4x+18 | | 10-3(1-7x)=-4x-8 | | (3+7i)+(6-5i)= |

Equations solver categories